MICROBIAL IDENTIFICATION AND ANALYSIS OF THE NUTRITIONAL CONTENT OF TRADITIONAL FOOD MATERIAL GATOT AND ITS MODIFICATION - Ambarsari, Imas
Gatot is a traditional processed food from cassava which has the potential as a substitute food but the production in small industries does not meet the standards so that the quality of the product is not guaranteed. This has the potential to have a negative effect on the body if it consumed. This study aims to identify microbes live in traditional gatot industries and to measure the nutritional value contained in them, compared to gatot modification. Gatot modification is made with the same condition but with 3 differents covers ie plastic, banana leaves and cloth. Gatot modification fermented in plastic cover shows gatot that are close to the gatot produced traditionally in Pacitan. Gatot’s color is black on the inside and outside, the texture is springy, the aroma is not stinging and the taste is savory. Gatot modification fermented in banana leaves and cloth shows different results from the traditional gatot, the black color was not formed, the texture was hard, and has a strong sour aroma. The identification of microbes showed Aspergillus flavus and Aspergillus niger, bacteria Pseudomonas aeruginosa, and lactic acid bacteria Pediococcus sp in traditional industrial gatot. Modified gatot fermented in plastic was identified lactic acid bacteria Pediococcus sp and yeast. Aspergillus flavus and Saccharomyces cerevicae were found in gatot with banana leave cover whereas in gatot covered with cloth was found Aspergillus niger. The nutritional content of modified gatot fermented in plastic wrap showed the most balanced results with the highest protein content compared to other samples, which was 3.8%. The protein content of modified gatot in plastic wrap increases compared to raw cassava. Analysis of heavy metal content of Pb and Cd were not found in all gatot samples, but the content of Fe was found at level 8.19 ppm in the traditional gatot industry while the gatot modified iron content was very low.